Potability of well water in Kirkuk city Iraq - Salah Aldeen Hassan Saeed; Riedh Abas Addul-Jabbar; Hajar Ali Shareef (Tikrit Journal of Pure Science, 2023)
The Kirkuk residents had resorted underground water as an alternative to the surface water the present study aims to indicate the quality of these water and demonstrates extent of their suitability drinking. For this purpose, 10 randomly distributed wells were measured, the average values 10 well were as follows: